Effect of phosphoric acid concentration used for etching on the microtensile bond strength to fluorotic teeth. Issue 35 (August 2018) - Gu, Mengqin; Lv, Linhu; He, Xiaoping; Li, Wangyang; Guo, Ling
Abstract : Abstract: To evaluate the effects of different etching concentrations of phosphoric acid on the microtensile bond strength of Adper Single Bond 2 to fluorotic teeth. Deidentified extracted teeth were collected, including 30 sound teeth, 30 teeth with mild fluorosis, 30 teeth with moderate fluorosis, and 30 teeth with severe fluorosis. The teeth in each group were randomly divided into 3 subgroups (n = 10) that were subjected to acid etching using 35%, 40%, or 45% phosphoric acid. Adper Single Bond 2 (3M, Saint Paul, MN) was used as the adhesive for bonding Z250 universal resin (3M) to the etched dental enamel. Microtensile testing was used to determine the bond strength. After the microtensile test, the fractured specimens were examined under scanning electron microscopy (SEM). Both dental fluorosis and concentrations of phosphoric acid significantly affected the microshear bond strength of Adper Single Bond 2 to dental enamel. The maximum bond strength was achieved by using 40% phosphoric acid. Failure analysis showed that most failures occurred at the bonding interface. The rates of failures at the bonding interface decreased as the degree of fluorosis increased and as the concentration of phosphoric acid increased from 35% to 45%. The bond strength of fluorosis tooth was lower than that of healthy tooth, the bond strength increased with the increasing concentration of phosphoric acid, but an excessively high acid concentration can conversely lead to an apparent decline in bond strength.